Ejecución presupuestal y su relación con el cumplimiento de objetivos en la sociedad de beneficencia de Iquitos, periodo 2020-2021 - Ramirez Angulo, Gabriela Solange (2024)
The objective of this research was to evaluate budget execution and its influence on the fulfillment of objectives of the Iquitos charitable society, period 2020 - 2021; With a type of quantitative study with a non-experimental design of descriptive explanatory scope, the population was made up of 71 people who work in charity in Iquitos, the documentary analysis and survey technique was used; According to the results, it shows that 77.5% of respondents state that they know the objectives of the Iquitos Charity Society, 80% that the objectives of the Iquitos Charity Society are aimed at improving people's quality of life; 62.5% state that the Iquitos Charity is characterized by always having management by objectives and 72.5% that the concept of quality of spending is to invest in the most needy population. It was also concluded that the fulfillment of physical goals in the year 2020 We have of the 11 activities 05 exceed 60%, 02 100% and 04 less than 50% in execution; With respect to 2021 we have, of the 11 activities, 05 exceed 60%, 02 100% and 04 less than 50% in execution; Regarding the financial goals, in 2020, of the 11 activities, 04 exceed 60%, 02 100% and 05 less than 54% in execution, with respect to 2021 we have 05 exceed 60%, 02 100% and 04 less than 45% in execution.